ESTRATEGIAS DE PROMOCIÓN Y SU IMPACTO EN LA AFLUENCIA TURÍSTICA DEL BALNEARIO “LOS CERRITOS” EN EL RECINTO CALABÍ, CANTÓN QUINSALOMA, AÑO 2022. - Leon Luna, Lilia Leonela (2022)
The "Los Cerritos" spa is located in the Quinsaloma Canton, it is a natural tourist destination, where its main attraction is the crystal clear river and also its delicious cuisine. This work determined the importance of promotion strategies and their impact on the tourist influx of the "Los Cerritos" spa in the Calabí area, Quinsaloma Canton, year 2022. The methodology applied is descriptive, bibliographic and field. To obtain information, a survey was carried out among the inhabitants of this canton to find out the level of satisfaction according to the tourist experience lived in the place, in addition, an interview was carried out with the leader of this community in order to know what type of strategies they use to promote the spa, in such a way that it allows to increase tourists and the economic development of the locality using new strategies of tourist promotion. The results suggest important evidence about the profile of the tourist who visits the "Los Cerritos" resort, the vast majority visit the place as a family, the most valued motivations were for recreation and holidays. The most valued variables are the satisfaction of the services according to the tourist experience they have had and if they recommend their acquaintances to visit the spa. Regarding the promotion carried out, it is not entirely adequate to capture the attention of tourists.